The Effect of Green Accounting and Corporate Social Responsibility (CSR) Implementation on Company Value in the Mining Sector - Dian Kusumaningrum; Chanif Kurnia Sari (PT. ELSHAD TECHNOLOGY INDONESIA, 2026)
The mining sector represents one of the most environmentally impactful industries globally, yet its role in national economies necessitates careful integration of sustainability practices. This study aims to analyze the effect of green accounting and Corporate Social Responsibility (CSR) implementation on company value in the mining sector listed on the Indonesia Stock Exchange (IDX) for the period 2018–2024. Employing a quantitative approach with panel data regression using the Fixed Effects Model on 30 mining companies (210 firm-year observations), this study measures green accounting through the Environmental Disclosure Index (EDI) based on GRI Standards 300, CSR through the CSR Disclosure Index (CSRDI) based on GRI Standards 200 and 400, and company value through Tobin’s Q. Control variables include firm size, profitability, leverage, firm age, institutional ownership, and capital intensity. The results demonstrate that green accounting has a positive and significant effect on company value (β = 0.0087, p < 0.01), and CSR disclosure similarly exerts a positive and significant effect (β = 0.0063, p < 0.05). Simultaneously, green accounting and CSR together significantly influence mining company value (Adjusted R² = 68.47%; F-statistic = 47.256, p < 0.01). These findings are grounded in stakeholder theory, legitimacy theory, and signaling theory, confirming that transparent environmental and social disclosures reduce information asymmetry and enhance investor confidence. This research provides empirical evidence for the importance of integrating environmental and social accountability into mining companies’ strategic frameworks to sustain long-term value creation.